2011
DOI: 10.1016/j.arthro.2010.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Treating Anterior Cruciate Ligament Tears in Skeletally Immature Patients

Abstract: Purpose To systematically review the current evidence for conservative and surgical treatment of anterior cruciate ligament (ACL) tears in skeletally immature patients. Methods A systematic search of PubMed, CINAHL, EMBASE, CCTR, and CDSR was performed for surgical and/or conservative treatment of complete ACL tears in immature individuals. Studies with less than six months of follow-up were excluded. Study quality was assessed and data were collected on clinical outcome, growth disturbance, and secondary jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
107
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 73 publications
0
107
0
1
Order By: Relevance
“…37,38 There is no consensus yet on the optimal surgical technique to best re-create the biomechanics of the native ACL. [39][40][41] Kocher et al 4 reported that 78% of surgeons surveyed had performed an ACL reconstruction in a skeletally immature patient but that no single technique predominated.…”
mentioning
confidence: 99%
“…37,38 There is no consensus yet on the optimal surgical technique to best re-create the biomechanics of the native ACL. [39][40][41] Kocher et al 4 reported that 78% of surgeons surveyed had performed an ACL reconstruction in a skeletally immature patient but that no single technique predominated.…”
mentioning
confidence: 99%
“…There is disagreement on how to approach ACL injuries in younger patients 1 2 4. When facing a patient with ACL injury and instability, many surgeons choose to conduct a more conservative treatment, while others wait for a higher level of skeleton maturity before they can proceed to reconstructing this structure.…”
Section: Discussionmentioning
confidence: 99%
“…These patients match Tanner’s classification for stages III and IV. However, for all patients with Tanner stages I and II, the debate continues and results in different approaches in the presence of the injury 1 2. Since these patients have a high physical development potential, transphyseal reconstruction might wound the growing physes and consequently result in sequelas during this further development.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent systematic review conducted by Vavken and Murray (2011) examined six studies using various physeal sparing surgical techniques and found that in children with a mean age of 12 years, no growth deformity was noted at an average of nearly 4 year post surgery follow-up. Hudgens and Dahm's (2012) review of the literature also supported that operative intervention increases knee stability and decreases the risk for further injury without significant risk of growth disturbance in the skeletally immature population.…”
Section: Special Considerations For Treatment Of Acl Injuries In the mentioning
confidence: 94%
“…The goal of these approaches is to protect the disruption of the growth plate to minimize the incidence of growth arrest and joint deformity (Hudgens & Dahm 2012;Vavken & Murray, 2011). The Division of Sports Medicine at Boston Children's Hospital (BCH) has developed a series of innovative age-specific physeal sparing surgical reconstruction techniques for use in treatment of ACL injury in patients with skeletal immaturity.…”
Section: Special Considerations For Treatment Of Acl Injuries In the mentioning
confidence: 99%